Promosi Perdamaian dan Harmoni: Kajian Pemanfaatan Warisan Kolonialisme Jepang di Bali Dalam Landskap Pariwisata (Jurnal Destinasi Pariwisata, 2026)
Japanese colonial heritage in Bali represents an underutilized cultural resource with the potential to support historical tourism and international soft power diplomacy. Although remnants of the Japanese occupation, including defensive tunnels, military cemeteries, wartime currency, weapons, and other historical artifacts, are still found across several regencies in Bali, many of these sites—particularly the Japanese caves-have experienced significant neglect and physical deterioration. This study aims to examine the potential of Japanese colonial heritage as a historical tourism attraction while promoting post-war reconciliation and strengthening Indonesia–Japan relations through soft power diplomacy. The research employs the Historical Cultural Tourism Landscape (HCTL) approach integrated with a historical diplomacy framework. Data were collected through field observations and in-depth interviews involving stakeholders representing the pentahelix model and were analyzed qualitatively. The findings reveal that Japanese colonial heritage sites possess not only historical significance but also strategic value as instruments of peace-building, reconciliation, and cultural diplomacy. A key finding of this study is the identification of storynomic tourism as an effective approach for transforming wartime heritage into tourism experiences that emphasize peace, tolerance, and shared historical memory, while simultaneously enhancing destination image and community participation. The study concludes that the revitalization and preservation of Japanese colonial heritage in Bali can strengthen sustainable historical tourism and serve as an effective medium for tourism-based soft power diplomacy, contributing to post-World War II reconciliation and international cultural cooperation